Population structure of yellowfin seabream (Acanthopagrus latus) in Central Vietnam through morphological and genetic analyses - NGUYEN TY; NGUYEN MY KIM NGAN; BUI VAN LOI; NGUYEN DUC THANH; NGUYEN XUAN HUY; TRAN VAN GIANG (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ty N, Ngan NMK, Loi BV, Thanh ND, Huy NX, Giang TV. 2025. Population structure of yellowfin seabream (Acanthopagrus latus) in Central Vietnam through morphological and genetic analyses. Biodiversitas 26: 2402-2409. The yellowfin seabream (Acanthopagrus latus (Houttuyn, 1782)) is a key species found along the coastal waters of Central Vietnam, where it plays an important role in local fisheries and ecosystems. Understanding its taxonomy and population dynamics is crucial for effective management and conservation. This study aimed to investigate the morphological and genetic characteristics of A. latus populations across three regions in Central Vietnam (Thua Thien Hue, Quang Binh, and Nghe An) to enhance knowledge of the species' diversity and structure. Morphological identification was based on 11 meristic counts, which revealed distinct species-specific traits, such as a slender, laterally flattened body, comb-like scales, and yellow fins. Genetic analysis of mitochondrial Cytochrome Oxidase I (mtCOI) sequences identified high genetic similarity (99.54%-100%) with references in NCBI GenBank, confirming the species identification. A total of six haplotypes were found, with Thua Thien Hue exhibiting the greatest genetic diversity, while Quang Binh showed no detectable nucleotide variation. AMOVA results indicated that 95.75% of the genetic variation occurred within populations, suggesting weak differentiation among regions (Fst = 0.04247). Neutrality tests indicated population expansion or purifying selection in Thua Thien Hue and Nghe An, while Quang Binh experienced a reduction in genetic variation. These findings offer valuable insights for the conservation and management of A. latus populations, emphasizing the need for strategies that account for both genetic connectivity and regional variability. The study also contributes to understanding the species' ecological interactions and provides a foundation for future research to monitor long-term changes in genetic diversity.